2021
DOI: 10.12669/pjms.37.7.4060
|View full text |Cite
|
Sign up to set email alerts
|

Lower mortality rate in health workers and their families infected with COVID-19 associated pneumonia in Quetta, Baluchistan

Abstract: Objectives: A bunch of pneumonia cases in Wuhan, China, was caused by a novel beta-corona virus, (COVID-19) in December 2019 from where it spread rapidly across the globe. The aim of the study was to find out relevant reasons and offered suggestions to reduce the risk of infection and check clinical outcomes of the infected healthcare workers. Methods: This study was conducted in COVID-19 Real Time Polymerase Chain Reaction (RT-PCR) laboratory, Bolan Medical Complex Hospital Quetta, Baluchistan from May … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…This corresponds with studies across the globe reporting severe COVID-19 on CTSS and higher values of CRP, LDH, D-dimers, Ferritin and worsening lymphopenia, including one of our own previous publications 17 , thus further validating our results. [18][19][20] Studies across Pakistan have also reported high inflammatory markers with higher severity of the disease which in turn increase the chances of developing complications and were associated with a higher mortality. 21 Francone reported no relationship between CT severity score and severe and critical disease groups; it may be attributed to small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds with studies across the globe reporting severe COVID-19 on CTSS and higher values of CRP, LDH, D-dimers, Ferritin and worsening lymphopenia, including one of our own previous publications 17 , thus further validating our results. [18][19][20] Studies across Pakistan have also reported high inflammatory markers with higher severity of the disease which in turn increase the chances of developing complications and were associated with a higher mortality. 21 Francone reported no relationship between CT severity score and severe and critical disease groups; it may be attributed to small sample size.…”
Section: Discussionmentioning
confidence: 99%